Corporate Turnaround in SME - case studies from CEE - Kurnas, Martin (2011)
The presented master thesis is intended to serve as a guide to the corporate turnarounds for small and medium enterprises. In the first part, the theoretical background related to corporate turnaround is outlined complemented with specific aspects of the CEE region and the Czech Republic. In the next part, a comprehensive turnaround framework based on theoretical research is developed. The final part presents a case study of a small Czech company that went through a turnaround and evaluates the company's turnaround actions from the perspective of suggested theoretical framework.